2009
DOI: 10.1038/onc.2009.389
|View full text |Cite
|
Sign up to set email alerts
|

Runx2 association with progression of prostate cancer in patients: mechanisms mediating bone osteolysis and osteoblastic metastatic lesions

Abstract: Runx2, a bone-specific transcriptional regulator, is abnormally expressed in highly metastatic prostate cancer cells. Here we identified the functional activities of Runx2 in facilitating tumor growth and osteolysis. Our studies demonstrate that negligible Runx2 is found in normal prostate epithelial and non-metastatic LNCaP prostate cancer cells. In the intra-tibial metastasis model, high Runx2 levels are associated with development of large tumors, increased expression of metastasis-related genes (MMP9, MMP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
319
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(338 citation statements)
references
References 41 publications
(74 reference statements)
17
319
0
2
Order By: Relevance
“…8,20 In breast carcinoma cells, expression of Runx2 is shown to be important in the positive regulation of angiogenic factors, and Runx2-regulated MMPs are functionally related to the invasion properties of breast cancer cells. 29,30 Likewise, our current study demonstrated that Runx2 expression is involved with positive regulation of angiogenic factors (VEGFA, VEGFC), MMP2 and EMTrelated molecules (SNAI2, SNAI3, TWIST1) in thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,20 In breast carcinoma cells, expression of Runx2 is shown to be important in the positive regulation of angiogenic factors, and Runx2-regulated MMPs are functionally related to the invasion properties of breast cancer cells. 29,30 Likewise, our current study demonstrated that Runx2 expression is involved with positive regulation of angiogenic factors (VEGFA, VEGFC), MMP2 and EMTrelated molecules (SNAI2, SNAI3, TWIST1) in thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Enhanced Runx2 expression in prostate cancer is associated with disease progression including higher Gleason scores. 8 In breast cancers with a high labeling index of Runx2, the clinical outcome of the breast cancer was worse; Runx2 is used as an independent prognostic factor in these patients. 23 An increasing number of studies have suggested oncogenic functions of Runx2 in carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of RUNX2 in MDA-MB-231 cells transplanted to bone decreases tumorigenesis and prevents osteolysis [140]. In the intra-tibial metastasis model, high RUNX2 levels is associated with development of large tumors and with increased expression of metastasis-related genes (MMP9, MMP13, VEGF, OPN) and secreted bone-resorbing factors (PTHrP, IL-8) [141].…”
Section: Cross Talk Between the Cancer Cell And The Bone Microenvironmentioning
confidence: 99%
“…In co-cultures RUNX2 promotes osteoclastogenesis in PC3 cells and inhibits osteoblast activity. [141]. Induction of RUNX2 in C4-2B cells enhances their invasiveness and promotes cellular quiescence by blocking the G1/S phase transition during cell cycle progression [142].…”
Section: Cross Talk Between the Cancer Cell And The Bone Microenvironmentioning
confidence: 99%